Biogeographic distribution patterns of the bacterial and archaeal communities in two seamounts in the Pacific Ocean - Liu, Ning-Hua; Ma, Jun; Lin, Si-Qi; Xu, Kui-Dong; Zhang, Yu-Zhong; Qin, Qi-Long; Zhang, Xi-Ying (Frontiers in Marine Science, 2023)
Seamounts are important components of seafloor topography and have a significant influence on the biogeographic distribution of marine microorganisms. However, current studies on the biogeographic distribution patterns of microorganisms in the ocean around seamounts are still inadequate. This study investigated the bacterial and archaeal communities present in the water column at various depths around the Kocebu and M5 seamounts located in the western Pacific Ocean using 16S rRNA gene high-throughput sequencing. The analyses showed that microbial communities had different alpha diversities and species compositions in samples from the same depth, and disruption of vertical stratification of microbes was observed in deep water layers at both seamounts. The stochastic processes dominated the microbial community assembly around two seamounts, for the Kocebu Seamount, drift accounted for 34.99% and 64.85% in the bacterial and archaeal community assembly processes, respectively; while the corresponding values for the M5 Seamount were 14.07% and 58.65%. Despite the low explanatory power of environmental variables for microbial communities, dissolved inorganic nitrogen was the most significant factor influencing the microbial community structure in seawater around seamounts. Overall, our results revealed that the presence of Kocebu and Running Title 2 M5 seamounts enhance the vertical mixing of microbial communities in the surrounding seawater, and stochastic processes dominate microbial community assembly. Considering the numerous seamounts in the global ocean, the impacts of seamounts on marine ecosystems and biogeochemical cycles may have been underestimated.